Problems of development of aesthetic culture at teenagers by means of the Kazakh decorative and applied arts - Kassimbekova, Barshagul; Tulekova, Gulmira; Korvyakov, Valeriy (Opción, 2018)
Now, special attention is paid to a problem of increase in level ofnational culture for realization of strategy for inclusion of kazakhstan amongthe world’s developed and competitive countries. An article is taken upquestions of formation of esthetic culture at teenagers by means of theirinvolvement to creative activity on the basis of folk traditional art. Animportant factor of esthetic development for the personality, its aspiration touniversal ideals and also participation in creation of cultural and historical achievements is folk art, in particular, decorative and applied arts.